C

Step by step explanation This is how I got the answer to your question and I gave you the solution I hope this helps you out

**Answer:**

**8 (2 g + 1) (4 g^2 - 2 g + 1)**

**Step-by-step explanation:**

Factor the following:

64 g^3 + 8

Factor 8 out of 64 g^3 + 8:

8 (8 g^3 + 1)

8 g^3 + 1 = (2 g)^3 + 1^3:

8 (2 g)^3 + 1^3

Factor the sum of two cubes. (2 g)^3 + 1^3 = (2 g + 1) ((2 g)^2 - 2 g + 1^2):

8 (2 g + 1) ((2 g)^2 - 2 g + 1^2)

1^2 = 1:

8 (2 g + 1) ((2 g)^2 - 2 g + 1)

Multiply each exponent in 2 g by 2:

8 (2 g + 1) (4 g^2 - 2 g + 1)

2^2 = 4:

Answer: 8 (2 g + 1) (4 g^2 - 2 g + 1)

**Answer:9/4**

**Step-by-step explanation: you can write this in algebra format. It becomes -3x+10=5x-8. From there, if you know simple algebra, it is very easy, and therefore x=9/4**